Efektivitas Program Beasiswa Sepuluh Sarjana per Desa di Kecamatan Kepohbaru Kabupaten Bojonegoro - Fitri Isma Widayanti; Weni Rosdiana (Perspektif Administrasi Publik dan hukum, 2026)
The Ten Scholars per Village Scholarship Program is a policy of the Government of Bojonegoro Regency aimed at improving access to and equity in higher education for rural communities through tuition fee (UKT) assistance. This study aims to analyze the effectiveness of the program implementation in Kepohbaru District using a descriptive qualitative approach and five effectiveness indicators proposed by Campbell J.P., namely program success, target achievement, satisfaction with the program, input and output levels, and goal attainment. Data were collected through interviews, observations, and documentation involving the Education Office, sub-district and village governments, scholarship recipient students, and the parents of scholarship recipients as informants. Data analysis was conducted based on Sugiyono’s model, including data reduction, data display, and conclusion drawing/verification, with validity tested through triangulation. The results show that the program has been implemented sustainably and contributes to supporting the continuity of higher education for rural students. Target achievement has been administratively fulfilled, although equity and quota distribution remain challenges. The level of satisfaction among recipients and parents is relatively good; however, there are still obstacles related to information dissemination and administrative processes. In terms of input and output indicators, the program is considered fairly effective as it consistently distributes financial assistance. Overall, the program is fairly effective in increasing access to and continuity of higher education, although improvements are still needed in terms of equity and implementation quality.